2009
DOI: 10.1007/s00018-009-0057-8
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Akt in neurite outgrowth

Abstract: The regulation of neuronal differentiation and neurite outgrowth is essential during development of the nervous system and is crucial in developing therapies to promote axon regeneration after nerve injury or in neurodegenerative diseases. The serine/threonine kinase Akt has been well documented to promote neuronal survival. More recently Akt has also been revealed as key mediator of several aspects of neurite outgrowth, including elongation, branching and calibre. Downstream of Akt, several substrates have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
143
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(152 citation statements)
references
References 92 publications
7
143
0
2
Order By: Relevance
“…Coffee-induced reduction of Akt phosphorylation may be responsible for the reduction of BDNF gene expression. Neurite outgrowth is one of the downstream effects of the Akt/CREB signaling cascade [30]. In this study, we showed that coffee significantly reduced the BDNF-induced neurite outgrowth.…”
Section: Discussionsupporting
confidence: 48%
“…Coffee-induced reduction of Akt phosphorylation may be responsible for the reduction of BDNF gene expression. Neurite outgrowth is one of the downstream effects of the Akt/CREB signaling cascade [30]. In this study, we showed that coffee significantly reduced the BDNF-induced neurite outgrowth.…”
Section: Discussionsupporting
confidence: 48%
“…*Po0.05, **Po0.005; Student's paired t-test Trib3 mediates death of NGF-deprived neurons N Zareen et al sparing effects we observed in Trib3 knockdown on processes of NGF-deprived neurons. 47 PI3K and Akt activation is a key pathway by which NGF promotes survival and NGF withdrawal reduces PI3K activity and Akt phosphorylation. [1][2][3]5 Why then are Trib3 and its actions on Akt required for neuron death after NGF deprivation?…”
Section: Discussionmentioning
confidence: 99%
“…Our results are summarized in Figure 8, which A previous report has demonstrated that pravastatin's stimulation of neurite outgrowth is mediated by reduction of RhoA signaling via inhibition of geranylgeranylation [12] . In addition to the Rho family proteins [31] , Akt has been revealed as a key mediator of several aspects of neurite outgrowth, including elongation, branching and caliber [15] . Several in vitro and in vivo studies provided evidence that statins activate the PKB/Akt pathway [3,32,33] .…”
Section: Discussionmentioning
confidence: 99%
“…Akt is the major effector of the phosphatidylinositol 3-kinase (PI3K) signaling pathway. Downstream of Akt, several substrates have been identified that are likely to play key roles in Akt-mediated neurite outgrowth, such as mammalian target of rapamycin (mTOR) and glycogen synthase kinase 3β (GSK-3β) [15] . mTOR is a serine/threonine protein kinase that regulates multiple cellular functions including neurite outgrowth.…”
Section: Introductionmentioning
confidence: 99%